2016
DOI: 10.1021/acs.chemrev.5b00723
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Synthesis of Cyclobutanes by Olefin [2 + 2] Photocycloaddition Reactions

Abstract: The [2 + 2] photocycloaddition is undisputedly the most important and most frequently used photochemical reaction. In this review, it is attempted to cover all recent aspects of [2 + 2] photocycloaddition chemistry with an emphasis on synthetically relevant, regio-, and stereoselective reactions. The review aims to comprehensively discuss relevant work, which was done in the field in the last 20 years (i.e., from 1995 to 2015). Organization of the data follows a subdivision according to mechanism and substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
418
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 885 publications
(470 citation statements)
references
References 894 publications
(1,331 reference statements)
5
418
0
9
Order By: Relevance
“…[1] Sie ermçglicht den gleichzeitigen Aufbau von zwei C-C-Bindungen und von bis zu vier stereogenen Zentren. Damit ähnelt sie der thermischen [4+ +2]-Cycloaddition, der DielsAlder-Reaktion, die einen ähnlich hohen Anstieg der Komplexitäte rlaubt.…”
Section: Von Allen Photochemischen Reaktionen Kommt Der [2+ +2]-unclassified
“…[1] Sie ermçglicht den gleichzeitigen Aufbau von zwei C-C-Bindungen und von bis zu vier stereogenen Zentren. Damit ähnelt sie der thermischen [4+ +2]-Cycloaddition, der DielsAlder-Reaktion, die einen ähnlich hohen Anstieg der Komplexitäte rlaubt.…”
Section: Von Allen Photochemischen Reaktionen Kommt Der [2+ +2]-unclassified
“…An optimization study showed that a ketone in the 2-position of the pyrrole was essential to enable lactam formation (Table 3, entries [1][2][3][4][5] and that a second ketone was actually deleterious to the process (entry 6). Although yields averaged around 50%, this in itself is quite remarkable as intense, high energy 254 nm UV light is used and the successful formation of 22 relies on 3-successive and independent photon mediated events.…”
Section: Scheme 4 Mechanism Of Tricyclic Imine Formationmentioning
confidence: 99%
“…The strained cyclobutane [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and oxetane [21][22][23] structures are important in organic synthesis. After Ciamician discovered the first example of photochemical [2+2] cycloaddition reaction, 24 Paternò, following Ciamician, reported the first photochemical [2+2] oxetane formation reaction using light irradiation.…”
Section: Introductionmentioning
confidence: 99%